The structural model of consumer intention and behaviour towards functional foods in Pakistan - Akhtar, Muhammad Farooq (2023)
Functional foods provide nutrients, prevent nutrition-related diseases and enhance physical and mental well-being. However, people in Pakistan face many nutritionrelated diseases. This study investigates the impact of procurement goals, (i.e., health, mood, convenience, sensory appeal, natural content, weight control, familiarity, price, and ethical concerns), approval goals, consumer attitudes, consumer subjective norms, consumer perceived behavioral control, consumer intentions and consumer behaviour towards functional foods. In addition, this study also investigates the moderating role of nutritional information between consumer intentions and behavior towards functional foods. A quantitative approach was used for the study, where data was collected through a questionnaire from 384 respondents in Pakistan through convenience sampling. Partial least squares-structural equation modeling (PLS-SEM) revealed a significant impact of procurement goals (i.e., health, familiarity, and price) on consumer attitude and between approval goals on consumer subjective norms. Moreover, consumer attitude and consumer subjective norms significantly influence consumer intention. Subsequently, consumer intention affects consumer behaviorntowards functional foods. However, insignificant relationships were found between procurement goals (i.e., mood, convenience, sensory appeal, natural content, weight control, ethical concerns) and consumer attitudes and between consumer-perceived behavioral control and consumer intention. In addition, nutritional information does not moderate the relationship between consumer intention and consumer behaviour toward functional foods. In terms of theoretical implications, this study applied the theory of reasoned goal pursuit (TRGP) with the addition of nutritional information derived from the heuristic system model in a single framework to assess consumer intentions and consumer behavior towards functional foods, as well as the moderating role of nutritional information in the Pakistan context. Marketing managers should emphasize the importance of procurement and approval goals as well as aspects of attitude, subjective norms, and perceived behavioral control in formulating effective strategies for the meaningful consumption of functional foods to address nutritional deficiencies and cure diseases.